Высшее профессиональное образование в республике Казахстан (сравнительный аспект) - Шалгимбеков, А.Б.; Чумак, Д. (My University, 2016)
he article is devoted to the problems of higher professional education in the country; there made the comparative analysis of academies in CIS and foreign countries.
Keywords: higher education; educational system; education, graduate; international co-operation